2009
DOI: 10.1080/02699050902997896
|View full text |Cite
|
Sign up to set email alerts
|

Anti-spastic effects of the direct application of vibratory stimuli to the spastic muscles of hemiplegic limbs in post-stroke patients

Abstract: The direct application of vibratory stimuli is an effective non-pharmacological anti-spastic treatment that could facilitate stroke rehabilitation. These results provide good evidence of potential short-term benefits of anti-spastic vibratory therapy in post-stroke patients in terms of decreased muscle tonus and improved motor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 24 publications
1
57
0
1
Order By: Relevance
“…Vibratory stimulation applied to the antagonist of a spastic muscle has been shown to decrease spasticity of a hemiplegic limb in previous studies 2. In addition, a recent study has shown that the application of vibratory stimulation directly to the spastic muscles decreases the spasticity in stroke patients in the subacute stages 3. Here we demonstrated that direct application of vibratory stimulation to the plantar fascia is more effective than direct application to the spastic muscles in the chronic neurological case.…”
Section: Discussionsupporting
confidence: 60%
“…Vibratory stimulation applied to the antagonist of a spastic muscle has been shown to decrease spasticity of a hemiplegic limb in previous studies 2. In addition, a recent study has shown that the application of vibratory stimulation directly to the spastic muscles decreases the spasticity in stroke patients in the subacute stages 3. Here we demonstrated that direct application of vibratory stimulation to the plantar fascia is more effective than direct application to the spastic muscles in the chronic neurological case.…”
Section: Discussionsupporting
confidence: 60%
“…550 Vibration applied to spastic muscle groups might be considered to reduce spasticity transiently, but it is not effective for long-term reduction of spastic hypertonia. [551][552][553] Injection of botulinum toxin is used commonly to treat upper limb spasticity in patients with stroke and is recommended in several recent review articles and previously published guidelines as an important tool in the comprehensive management of poststroke spastic hypertonia. 149,[554][555][556][557] Injections of botulinum toxin A can reduce spasticity significantly as measured by the Ashworth scale.…”
Section: Spasticitymentioning
confidence: 99%
“…Manganotti and Amelio explained this was due to the effects of mechanical vibratory stimulation and spinal cord excitability 21) . Noma et al suggested that decreasing spasticity was caused by a decrease in F-wave amplitude 19) . Therefore, a probable explanation for the spasticity decrease seen in our study is that the vibratory stimulation decreased the excitability of the α-motor neurons through the activation of presynaptic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Murillo et al reported that spasticity decreased after vibratory stimulation of rectus femoris muscles that had 18) . Two studies report a mitigation of spasticity using clinical or neurophysiological evaluations 18,19) . However, the development of Myotonometer has enabled a new approach that allows quantitative measurement of the mechanical elements in the soft tissues of spastic muscles 9,20) .…”
Section: Discussionmentioning
confidence: 99%